Statistical Investigation of High Culture Contamination Rates in Mycobacteriology Laboratory - Mohammed Adam, Muatsim Ahmed; Ebraheem, Rasha Sayed Mohammed; Bedri, Shahinaz Ahmed (Frontiers in Microbiology, 2022)
Background Culture of Mycobacterium tuberculosis remains the gold standard in mycobacteriology laboratory, constrained by the greatest risk of contamination; therefore contamination rate is an important key performance indicator (KPI) for laboratory monitoring and evaluation processes. Aim This study aimed to investigate the predictors that contribute to elevating contamination rates in the Sudan national tuberculosis reference laboratory. Method A laboratory-based retrospective study was applied; TB culture register-book was carefully reviewed, data from 2nd January to 31st December 2019, were entered, cleaned, and analyzed using IBM SPSS 20. A multivariate logistic regression model was performed to examine two dependents variables, the massive contamination rate and the rate of contamination by bottle. Results It has been found that in 2019 contamination rates are frequently higher, the highest rate was recorded in January and November 28.2%; 25.2% respectively. August is an exception with an accepted contamination rate of 4.6%. Of 1149 specimens requested for culture, a number of 945(82.2%) samples are eligible to be included in multivariate logistic regression analysis. The operator of the experiment was significantly associated with a high contamination rate p-value 0.007; odds ratio (OR) 0.280 (0.111-0.707). The correlation between the contamination rate by bottle and the massive contamination rate is significant; p-value 0.01. Conclusion The study concludes that high culture contamination is the greatest risk of the quality of laboratory service and can end to either the loss of specimens or delay in the decisions of initiating patients' treatment. In addition, the low quality of data is increasing the uncertainty and undermine the measurement of key performance indicators. Further laboratory personnel who are performing culture of M tuberculosis should have to be in the same level of proficiency.